2021
DOI: 10.1123/jsm.2020-0194
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence in the Study of Shirking in Major League Baseball

Abstract: This paper uses Major League Baseball data to examine the relationship between years remaining on player contracts and player performance. There is a potential for moral hazard to arise in this principal–agent relationship as the player may choose a less than optimal level of effort from the perspective of team management when the player has many guaranteed years remaining. A player fixed-effects estimation strategy, which finds a significant negative relationship between years remaining and performance, is em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Solow and Krautmann (2020) compare the economic cost and estimated benefits of a contract and finds that teams overpay on average and more so for longer contracts. Paulsen (2021) finds a significant negative relationship between years remaining on player contracts and player performance with the baseball players data. Some studies use data on sport players to explore the effect of efficiency on salary (Bodvarsson & Brastow, 1998; Harder, 1992; Inoue et al, 2013; Scott et al, 1985; Scully, 1974; Soebbing et al, 2016; Wallace, 1988), but these studies employ improper models.…”
Section: Introductionmentioning
confidence: 77%
“…Solow and Krautmann (2020) compare the economic cost and estimated benefits of a contract and finds that teams overpay on average and more so for longer contracts. Paulsen (2021) finds a significant negative relationship between years remaining on player contracts and player performance with the baseball players data. Some studies use data on sport players to explore the effect of efficiency on salary (Bodvarsson & Brastow, 1998; Harder, 1992; Inoue et al, 2013; Scott et al, 1985; Scully, 1974; Soebbing et al, 2016; Wallace, 1988), but these studies employ improper models.…”
Section: Introductionmentioning
confidence: 77%
“…On-Base Plus Slugging Average is used in Hakes and Turner (2008), Krautmann and Donley (2009), Krautmann and Solow (2009) and O’Neill (2013). Paulsen (2021) uses Wins Above Replacement (WAR), while Paulsen (2022) uses Weighted On-Base Average in assessing performance using game level data. While evidence is mixed in the less recent literature, the most recent works, which include O’Neill (2013), Paulsen (2021, 2022) all find evidence of shirking using player fixed effects with panel data to address positive selection into multiyear contracts.…”
Section: Literaturementioning
confidence: 99%
“…Shirking, the suboptimal exertion of effort arising from moral hazard in labor market settings, has been studied in several labor market settings, but has received a lot of attention in sports and notably in the setting of Major League Baseball. Most authors, including recent works like O’Neill (2013) and Paulsen (2021) have measured shirking by looking at measures of on-field performance. Both O’Neill (2013) and Paulsen (2021) used player fixed effects regressions with panel data and found an inverse relationship between years remaining on a contract and performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to research on the relationship between worker productivity and dismissal threats, previous research on contract‐related incentive effects has produced mixed evidence. Some studies found clear evidence of this opportunistic behavior by players (Frick, 2011; Krautmann & Solow, 2009; O'Neill, 2013; O'Neill & Deacle, 2019; Paulsen, 2021; Scoggins, 1993; Stiroh, 2007), some found no clear evidence of this behavior (Gómez et al, 2019; Krautmann, 1990; Maxcy et al, 2002), and some found that the relationship between player performance and contract details depended on how performance was measured (Berri & Krautmann, 2006; Krautmann & Donley, 2009; White & Sheldon, 2014). Most of the literature investigating the potential for opportunistic behavior among professional athletes has focused on professional baseball, basketball, or soccer players.…”
Section: Introductionmentioning
confidence: 99%